The Role of Accounting Information Systems in Strengthening Revenue Budget Management and Village Expenditure in Indonesia - Angginun Juwita Sari Harahap; Ratu Nur Susan Vonita; Prasasti Nuraeni; Fauzan Romadhian Khairi (Westscience Press, 2025)
This study seeks to ascertain and elucidate the implementation of accounting information systems in the management of village revenue and expenditure budgets, as well as to identify the challenges and solutions associated with these systems in Indonesia, specifically through a case study of Karacak Village, Leuwiliang District, Bogor Regency. The utilization of accounting information system (AIS) in the administration of revenue budget management and village expenditure (APBDes) is evaluated according to the AIS components delineated by Romney & Steinbart, AIS efficacy based on TAM theory with measurement elements suggested by James Wetherbe, and internal control components as outlined by the Committee of Sponsoring Organizations of the Treadway Commission (COSO). This study employs a qualitative methodology grounded in an interpretative paradigm utilizing a phenomenological approach. This study included data gathering strategies including interviews with main informants and supporting informants, as well as documentation. The results of the study indicate that the application of internal control using the thirteen components of COSO, the Karacak Village government has 61.53% run well and effectively, and 38.46% has not run effectively The findings of this investigation suggest that Karacak Village Government has implemented AIS in managing the APBDes in accordance with Permendagri/20/2018 by measuring from the AIS component, AIS performance, and internal control components, in addition to the obstacles faced in the application of AIS in managing APBDes related to the APBDes planning stage and internal control.